Encyclopedia of the Horse - Peplow, Elizabeth (London : Bounty, 2002)
The ultimate guide to the world of horses and horse riding, this book traces the development of the horse and its integration into early society, looks at how countries developed their own breeds and much more.
Originally published: London: Hamlyn, 1998.
Includes index.
Keywords: Horses; Farming and Country Life